KONSEP MODERASI ISLAM DAN ETIKA KEUTAMAAN ARISTOTELES - Nia'am, M Khusnun; Lestari, Puput Dwi (Academic Journal of Islamic Principles and Philosophy, 2020)
This article aims to describe and analyze issues related to Islamic moderation in the perspective of Aristotle's ethics. Departing from the phenomenon of Islamic rigidity brought by a group with a one-sided truth claim that is not in line with the essence of Islam as a blessing for the universe. Truth claimÂ contrasts to the concept of moderation in Islam. This article will compare the concept of moderation in Islam to Aristotleâ€™s concept of the ethics of virtue. Thus it is interesting to see the concept of ethics in the context of religious moderation. Applying a descriptive-analysis approach, this article shows that the concept of Islamic moderation has in common with Aristotle's view of virtue. Aristotle views that moderation is a wisdom since it comes from the experience of thinking by combining the two choises until becoming a habit. It is the core argument of this article that tries to position reason and theory as a nature for justice.